Engaging Displaced Nepali Workers in Post COVID-19 Situations: A Call for Action - Parajuli, Mahesh Nath; Gautam, Suresh; Dhakal, Rebat Kumar; Bajracharya, Jiwak Raj; Paudel, Tikaram; Acharya, Laxman; Paudel, Prakash Kumar (Journal of Education and Research, 2020)
As the battle against COVID-19 is on-going, it may not be suitable a time to worry about the world of work in post-COVID-19 situations. Nevertheless, it is logical for academics to envision ways out in response to the socio-economic challenges that we have to face. Through this editorial, we portray some strategies for engaging the displaced Nepali workers in post-COVID-19 situations.